"PAULOWNIA SPECIES" GROWING FOR SAPLINGS IN POTS IN ROMANIA: TECHNOLOGICAL ASPECTS AND COMPARATIVE EXPENSES, INCOMES AND PROFIT - Agatha POPESCU; Liviu SABAU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to comparatively analyze the economic efficiency of Paulownia Species, Shan Tung variety, grown for producing 10,000 saplings in pots at SC Galya 3000 SRL, Cerneteaz Commune, Timis County, Romania in the year 2016. The research includes three alternatives for producing 10,000 saplings in pots as follows: V1- saplings in pots 7x7x8 cm, V2- saplings in pots of 19 cm, and V3-saplings in pots of 36 cm. In case of V3, the production cost for 8 months to produce saplings of 1-1.5 m height in a pot of 36 cm was Lei 8.95, 2 times higher compared to V2, where the cost per sapling of 50 cm in a pot of 19 cm was Lei 4.06 and 7.16 times higher than in case of V1, where the cost per sapling of 4 cm in a small pot of 8 cm was Lei 1.25. The income is 6 times higher in case of V3 compared to V1 and 2 times higher compared to V2, and as a consequence, the gross profit increases from V1 to V3, while the profit rate decreases from 300.14 % in case of V1 to 235.04 % in case of V3. Therefore, the profit rate is enough high to consider Paulownia growing a real business for all the three variants. As a final conclusion, Paulownia tree growing is a real business for farmers interested to get income and profit in a short period of time varying from1.5 months to 8 months. Also, the plants could be grown in plantations for fuel and furniture wood whose price is much higher if the wood is sold in the international market.